Removal of Remazol Yellow from Textile Industry Wastewater by Quaternary Ammonium Polymer - Agsa Ardelia Musnamar; Aster Rahayu; Dhias Cahya Hakika; Nafira Alfi Zaini Amrillah; Hutri Puspita Sari; Syahrani Pramia Lestari; Wah Lim Lee (Universitas Darussalam Gontor, 2025)
The use of Remazol Yellow dyes in the textile industry will produce waste that is mutagenic and carcinogenic. The stable nature of remazol causes Remazol Yellow to not be easily degraded photolytically or chemically. If the waste is directly disposed of into water bodies, it will accumulate and last for a long time. Adsorption is one of the textile waste processing methods that is widely used because it is an effective textile waste processing method for degrading dyes, does not require large costs, the adsorbent can be used several times, and the process is simple. This research seeks to establish the appropriate contact duration, temperature, and ideal adsorption concentration of quaternary ammonium polymers within a Remazol Yellow dye solution. The process of dye adsorption by varying the time (10; 20; 30; 40; 50; and 60) minutes, temperature (25, 30, 40, 50, 60, and 70)°C, and initial concentration (10, 20, 30, 40 and 50) ppm. The adsorption of the filtrate was then measured using a UV-Vis Spectrophotometer instrument. The dye in the Remazol Yellow solution was successfully adsorbed by the quaternary ammonium polymer with optimum conditions at 20 minutes, a temperature of 25°C, and an initial concentration of 10 ppm. The optimum adsorption percentages obtained were 98.44%, 98.54%, and 98.25% respectively. From these results, quaternary ammonium polymers can be further applied for dye degradation. Morphological analysis was carried out using a Scanning Electron Microscope (SEM) instrument, obtaining a distribution of polymer pore values after adsorption in the range of 0.84-2.09 µm. The quaternary ammonium polymer structure is in the form of a solid lump after undergoing adsorption of Remazol Yellow.